2D Animation Character Design for Sang Penunggu Bulan Folk Tales from West Java - Allison, Andy; Fuad, Ahmad (Universitas Pembangunan Jaya, 2023)
Indonesia is rich in folklore from various provinces. One of these provinces is the province of West Java which is rich in folklore. However, among the folklore in the province of West Java, the fairy tale Nyi Anteh Sang Penunggu Bulan is still little known to the wider public, especially children. Folklore of Sang Penunggu Bulan should be introduced to children from an early age. Folklore characters do show compassion which is useful as a means of education and introspection in children. For example, the character Nyi Anteh has a very good personality. All the goodness contained in the character of Nyi Anteh can be presented to children in an interesting way thanks to information technology. One information technology that is currently developing rapidly and is able to attract the attention and interaction of people who see it is the field of 2D animation. The research method used is descriptive by collecting data through literature to describe the pre-production, production, and post-production stages. With animation, things that are difficult to express in words will become simple and easy to understand when listening to animated video content. Therefore, it is necessary to design a 2D animated character for Nyi Anteh that can convey the personality and traits inherent in Nyi Anteh through her facial expressions and body movements, so that she can be a role model for good behavior for children to follow every day.